Essential role of mesolimbic brain-derived neurotrophic factor in chronic social stress-induced depressive behaviors - Koo, Ja Wook (Biol Psychiatry, 2015)
BACKGROUND: Previous work has shown that chronic social defeat stress (CSDS) induces increased phasic firing of ventral tegmental area (VTA) dopamine neurons that project to the nucleus accumbens (NAc) selectively in mice that are susceptible to the deleterious effects of the stress. In addition, acute optogenetic phasic stimulation of these neurons promotes susceptibility in animals exposed to acute defeat stress. These findings are paradoxical since increased dopamine (DA) signaling in NAc normally promotes motivation and reward, and the influence of chronic phasic VTA firing in the face of chronic stress remains unknown. METHODS: We used CSDS with repeated optogenetic activation and pharmacological manipulations of the mesolimbic VTA-NAc pathway to examine the role of brain-derived neurotrophic factor (BDNF) and DA signaling in depressive-like behaviors. BDNF protein expression and DA release were measured in this model. RESULTS: Pharmacological blockade of BDNF-TrkB signaling, but not DA signaling, in NAc prevented CSDS-induced behavioral abnormalities. Chronic optogenetic phasic stimulation of the VTA-NAc circuit during CSDS exacerbated the defeat-induced behavioral symptoms, and these aggravated symptoms were also normalized by BDNF-TrkB blockade in NAc. The aggravated behavioral deficits induced by phasic stimulation of the VTA-NAc pathway were also blocked by local knockdown of BDNF in VTA. CONCLUSIONS: These findings show that BDNF-TrkB signaling, rather than DA signaling, in the VTA-NAc circuit is crucial for facilitating depressive-like outcomes after CSDS, and establish such BDNF-TrkB signaling as a pathological mechanism during periods of chronic stress.